Autonomous Mobile Robot Exploration in Negative Obstacle Environment - Keskin, Numan; Uslu, Erkan; Cakmak, Furkan; Altuntas, Nihal; Amasyali, M. Fatih; Yavuz, Sirma (IEEE, 2017)
Restricted 3D simultaneous localization and mapping (SLAM) can be achived in an environment that has negative and positive obstacles, using a 2D SLAM and a 3D mapping together. Exploration can utilize 2D navigation, which uses a 2D map constructed with respect to 3D map obstacles both negative and positive, and free areas. Robocup, Rescue League, Exploration 4 competition is designed to measure real platform autonomous mobile robot exploration capabilities in an negative obstacle scene. In this paper aforementioned exploration approach is implemented in a simulation environment created in Gazebo similar to Exploration 4 arena, using Robot Operating System (ROS).
Keywords: 2D localization; 3D mapping; 2D navigation; 2D exploration; OctoMap; autonomous mobile robot; negative obstacles; Acoustics; Computer Science; Engineering; Telecommunications